Enhancing Elementary School Students’ Pronunciation Skills through Flashcard Pronunciation Drills as an Autonomous Learning-Based Educational Games - Genoveva Dua Eni; Yos Yosando Liem (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research aimed to (1) improve students’ pronunciation skills through the implementation of Flashcard Pronunciation Drills based on educational games designed according to the principles of autonomous learning; (2) foster students’ learning autonomy in English learning by providing opportunities for them to plan, control, and evaluate their own learning process; (3) enhance students’ motivation and self-confidencein using English, particularly in pronouncing words and sentences accurately, through interactive, enjoyable, and contextual learning activities; and (4) encourageteachers’ creativity in designing and conducting English lessons using simple yet effective media that can be implemented in schools with limited technological facilities. The research method used was Classroom Action Research (CAR), chosen because it aligned with the research objectivesto improve students’ pronunciation skills while also understanding changes in their learning behavior and level of autonomy during the learning process. The test scores were analyzed to identify changes in the students’ average performance before and afterimplementing the learning media, particularly in aspects of articulation accuracy, intonation, and fluency. The research subjects consisted of 13 fourth-grade students at SDN XXXIX Hubing, located in TekaIku Village, KangaeSub-district, Sikka Regency, an area with very limited internet access; thus, non-digital media became the most relevant option to support autonomous learning.Data were collected through four main instruments: (1) pronunciation ability tests (pre-test and post-test) to measure students’ learning outcomes, (2) observation sheets to monitor student activity and participation during learning, and (3) teacher interviews to obtain insights into behavioral changes and media effectiveness. The learning process was carried out in two cycles over four weeks, involving Flashcard Pronunciation Drillsaccompanied by educational game activities such as wordmatching, sound repetition, and pronunciation challenge.The results showed a significant improvement in students’ pronunciation ability, both quantitatively and qualitatively. Quantitatively, the average student score increased from 56.77 (pre-cycle) to 81.77 (post-cycle), indicating a gain of 25 points. Qualitatively, students became more active, more willing to pronounce new words, and were able to correct their pronunciation errors independently through repeated practice using flashcards. Teachers also reported that this medium was easy to implement, efficient in classrooms with limited facilities, and effective in creating a fun and interactive learning atmosphere.In addition, to enhance learning outcomes, the media also fostered students’ independence, self-confidence, and learning motivation.